2000
DOI: 10.1002/1097-0231(20001215)14:23<2220::aid-rcm155>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

On-probe sample pretreatment for the detection of proteins above 15 KDa from whole cell bacteria by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: A rapid methodology is described for the enhancement of the signal‐to‐base‐line (S/B) ratio of high molecular weight protein signals from whole cell bacteria analyzed by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOFMS). The procedure involves depositing growing bacteria colonies from culture dishes directly onto the MALDI probe followed by treatment of the sample spot with a 2 µL aliquot of 40% ethanol prior to the addition of a ferulic acid matrix solution (12.5 mg di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 28 publications
2
74
0
Order By: Relevance
“…They describe 2,6-dihydroxyacetophenon, which is an alternative for 2,4,6-THAP, as an unsuitable matrix [50]. Similar inconsistent observations are described for the analysis of whole bacterial cells [8,27,28,[51][52][53][54]. Unfortunately, these results are difficult to compare due to strong structural differences between bacterial spores and their vegetative cells or fungal spores.…”
Section: Choice Of Maldi-matrixmentioning
confidence: 99%
“…They describe 2,6-dihydroxyacetophenon, which is an alternative for 2,4,6-THAP, as an unsuitable matrix [50]. Similar inconsistent observations are described for the analysis of whole bacterial cells [8,27,28,[51][52][53][54]. Unfortunately, these results are difficult to compare due to strong structural differences between bacterial spores and their vegetative cells or fungal spores.…”
Section: Choice Of Maldi-matrixmentioning
confidence: 99%
“…Numerous studies were reported to expand the upper mass range for bacterial proteins obtained from whole cell MALDI-TOF-MS analysis [7,9]. The influence of matrix, solvent, and spotting techniques on the mass range and the quality of the MALDI spectra were reported.…”
mentioning
confidence: 95%
“…A majority of the early research published on whole cell bacterial MALDI analysis described protein profiles up to 30 kDa [2,3]. The signals in this range were attributed to cellular proteins or cell wall associated proteins [8,9].Numerous studies were reported to expand the upper mass range for bacterial proteins obtained from whole cell MALDI-TOF-MS analysis [7,9]. The influence of matrix, solvent, and spotting techniques on the mass range and the quality of the MALDI spectra were reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DHB and CHCA are usually optimal for the detection of lower mass ions (Hathout et al, 2000;Williams et al, 2003;Ruelle et al, 2004) with a detection up to 10 kDa when the proper solvent is used. Both SA and FA have been shown to be better for the detection of higher mass ions (above 15 kDa) (Madonna et al, 2000;Conway et al, 2001;Ruelle et al, 2004;Vargha et al, 2006) but provide a lower sensitivity than CHCA (Wang et al, 1998;Ruelle et al, 2004).…”
Section: Techniquementioning
confidence: 99%